(untitled) (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2017)
Â The development of today’s technology so rapidly, this development affects the audio-visual media one of which is video games. The aim of this study are: 1) to analyze the differences influence the level of violent video game playing element to the level of adolescent aggressive behavior, 2) to analyze the influence of personal factors as differences in behavior-forming element violent video games to the level of adolescent aggressive behavior, 3) to analyze differences in the effect of factors situational as forming behavior of violent video game playing element to the level of adolescent aggressive behavior. The analysis in this study uses cross tabulation, the statistical test Mann-Whitney and Kruskal-Wallis with a 5% significance level. The results showed that there are differences in the level of situational and gender differences on the level of play behavior element violent video games; and there are differences in the level of playing video games behavioral element of violence against adolescent aggressiveness level. Keywords: audio-visual media, development of technology Â ——————————————————————————————- ABSTRAK Perkembangan teknologi saat ini begitu pesat, perkembangan ini mempengaruhi media audio-visual salah satunya adalah video game. Tujuan dari penelitian ini adalah: 1) untuk menganalisis perbedaan yang memengaruhi elemen tingkat kekerasan bermain video game ke tingkat perilaku agresif remaja, 2) untuk menganalisis pengaruh faktor pribadi sebagai perbedaan dalam elemen perilaku pembentuk video game kekerasan untuk tingkat perilaku agresif remaja, 3) untuk menganalisis perbedaan pengaruh faktor situasional sebagai pembentuk perilaku bermain video game unsur kekerasan ke tingkat perilaku agresif remaja. Analisis dalam penelitian ini menggunakan tabulasi silang, uji statistik Mann-Whitney dan Kruskal-Wallis dengan tingkat signifikansi 5%. Hasil penelitian menunjukkan bahwa ada perbedaan dalam tingkat perbedaan situasional dan jenis kelamin pada tingkat perilaku bermain elemen video game kekerasan; dan ada perbedaan dalam tingkat bermain video game unsur perilaku kekerasan terhadap tingkat agresivitas remaja. Kata kunci: media audio-visual, perkembangan teknologi